Asynchronous Variation in the Quaternary East Asian Winter Monsoon Associated With the Tropical Pacific ENSO‐Like System. Issue 12 (28th June 2019) - Zhao, Debo; Wan, Shiming; Song, Zhaoyang; Gong, Xun; Zhai, Lina; Shi, Xuefa; Li, Anchun
Abstract: Quaternary East Asian winter monsoon (EAWM) evolution has long been attributed to high‐latitude Northern Hemisphere climate change. However, it cannot explain the distinct relationships of the EAWM in the northern and southern East Asian marginal sea in paleoclimatic records. Here we present an EAWM record of the northern East China Sea over the past 300 ka and a transient climate simulation with the Kiel Climate Model through the Holocene. Both proxy record and simulation suggest anticorrelated long‐term EAWM evolution between the northern East China Sea and the South China Sea. We suggest that this spatial discrepancy of EAWM can be interpreted as El Niño–Southern Oscillation (ENSO)‐like controlling, which generates cyclonic/anticyclonic wind anomalies in the northern/southern East Asian marginal sea. This research explains much of the controversy in nonorbital scale variability of Quaternary EAWM records in the East Asian marginal sea and supports a potent role of tropical forcing in East Asian winter climate change. Plain Language Summary: The modern East Asian winter monsoon (EAWM) is influenced by the combined effects of both the high‐latitude Northern Hemisphere (e.g., Siberian High) and the low‐latitude Western Pacific (e.g., El Niño–Southern Oscillation) and plays a major role in regulating atmospheric energy of East Asia and even the Northern Hemisphere. Its anomalies may cause extremely cold/warm winter weather or climate events, which result in profound societal and economic influences on the densely populated region of East Asia. Especially, some studies found the EAWM displays spatial discrepancies in northern and southern East Asia and can result in a colder/warmer north corresponding to a warmer/colder south. Our study shows anticorrelations of EAWM evolution between the northern East Asian marginal sea and the South China Sea since the late Quaternary. We suggest that such spatial discrepancies of EAWM evolution were controlled by El Niño–Southern Oscillation‐like processes in the tropical Pacific. During El Niño‐like conditions, the anomalous northwesterlies in the northern East Asian marginal sea led to a strengthened EAWM in this region. In contrast, anomalous southwesterlies in the South China Sea favored the occurrence of a weakened EAWM. The opposite situation occurred under La Niña‐like conditions. Key Points: Clay minerals in northern Okinawa Trough were derived from Yellow River and Kyushu Reversed EAWM evolution in the northern and southern East Asian marginal sea was revealed ENSO‐like processes cause spatial discrepancy of Quaternary EAWM evolution